Unraveling the intricate relationship between lipid metabolism and oncogenic signaling pathways - Khan, Fahad; Elsori, Deena; Verma, Meenakshi; Pandey, Shivam; Obaidur Rab, Safia; Siddiqui, Samra; Alabdallah, Nadiyah M.; Saeed, Mohd; Pandey, Pratibha (Frontiers in Cell and Developmental Biology, 2024)
Lipids, the primary constituents of the cell membrane, play essential roles in nearly all cellular functions, such as cell-cell recognition, signaling transduction, and energy provision. Lipid metabolism is necessary for the maintenance of life since it regulates the balance between the processes of synthesis and breakdown. Increasing evidence suggests that cancer cells exhibit abnormal lipid metabolism, significantly affecting their malignant characteristics, including selfrenewal, differentiation, invasion, metastasis, and drug sensitivity and resistance. Prominent oncogenic signaling pathways that modulate metabolic gene expression and elevate metabolic enzyme activity include phosphoinositide 3-kinase (PI3K)/AKT, MAPK, NF-kB, Wnt, Notch, and Hippo pathway. Conversely, when metabolic processes are not regulated, they can lead to malfunctions in cellular signal transduction pathways. This, in turn, enables uncontrolled cancer cell growth by providing the necessary energy, building blocks, and redox potentials. Therefore, targeting lipid metabolism-associated oncogenic signaling pathways could be an effective therapeutic approach to decrease cancer incidence and promote survival. This review sheds light on the interactions between lipid reprogramming and signaling pathways in cancer. Exploring lipid metabolism as a target could provide a promising approach for creating anticancer treatments by identifying metabolic inhibitors. Additionally, we have also provided an overview of the drugs targeting lipid metabolism in cancer in this review.